Cost-Utility Analysis of Heberprot-P as an Add-on Therapy to Good Wound Care for Patients in Slovakia with Advanced Diabetic Foot Ulcer - Tesar, Tomas; Szilberhorn, Laszlo; Nemeth, Bertalan; Nagy, Balazs; Wawruch, Martin; Kalo, Zoltan (Frontiers in Pharmacology, 2017)
Objectives: To explore whether Heberprot-P (an epidermal growth factor) is a cost-effective option for the treatment of advanced diabetic foot ulcer as an add-on therapy to good wound care (GWC) in Slovakia from the perspective of health care payers. Methods: A Markov model was constructed to compare the costs and effects of Heberprot-P plus GWC to those of GWC alone from the perspective of health care payers. The 52-week clinical trial period was extended to five- and 10-year time horizons. Transition probabilities were calculated based on a previous clinical trial of Heberprot, utility values were derived from the scientific literature, and cost vectors were collected from the General Health Insurance Fund database in Slovakia. A one-way deterministic sensitivity analysis was employed to explore the influence of uncertainty for each input parameter on the incremental cost-effectiveness ratio (ICER). Results: Based on the ICER threshold of €30,030 per quality-adjusted life year (QALY) recommended by the Slovak Ministry of Health, Heberprot-P therapy plus GWC is not a cost-effective alternative to GWC alone over a 10-year time horizon. The ICER increases if a longer time horizon is applied, as the incremental costs are similar, but the aggregated utility gain from avoided amputation is lower. Based on the sensitivity analysis, the utility multiplier for the health state “no ulcer after small amputation” had the most impact on the ICER; however, the model was robust to changes in all input parameters. Conclusions: Heberprot-P, as an add-on therapy to GWC in the treatment of advanced diabetic foot ulcer, is not a cost-effective alternative to GWC alone. However, if the unit cost of Heberprot-P were to be reduced to <€273, its ICER would be <€30,030.